Pemahaman Peternak Sapi Tentang Kandungan Nutrisi Limbah Pertanian dalam Efisiensi Pakan - Solikin, Nur; Andaruisworo, Sapta; Hasim, Ahmad Nur (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
The availability of animal feed is one of the main factors that must be considered by farmers to achieve business success. Service activities aim to assist farmers in understanding the use of agricultural waste as a source of feed as a cost efficiency solution. The activity method uses a participatory approach, the service team as a facilitator or study partner and farmers as active subjects in the activity. The activity was carried out in the Sri Lestari farmer/livestock group, Semen Village, Semen District, Kediri Regency. The results obtained in this activity are that cattle breeders do not understand the nutritional content of feed from agricultural waste, but most of the farmers have used agricultural waste for animal feed. In conclusion, the understanding of farmers regarding the nutrients contained in plant waste needs to be continuously improved, and further activities are needed, especially techniques for improving animal feed nutrition.